Artemisinin-naphthoquine combination therapy for uncomplicated pediatric malaria: A tolerability, safety, and preliminary efficacy study - Benjamin, J.; Moore, Brioni; Lee, S.; Senn, M.; Griffin, S.; Lautu, D.; Salman, S.; Siba, P.; Mueller, I.; Davis, T. (American Society for Microbiology, 2012)
Artemisinin-naphthoquine (ART-NQ) is a fixed-dose coformulated antimalarial therapy recommended as a single-dose treatment and marketed in Papua New Guinea among other tropical countries. We conducted a tolerability, safety, and efficacy study of ART-NQ for Papua New Guinean children aged 5 to 12 years with uncomplicated malaria, comparing single-dose ART-NQ (15 and 6 mg/kg of body weight) given with water (group 1; n = 15), single-dose ART-NQ (22 and 9 mg/kg) given with milk (group 2; n = 17), or two daily doses of 22 and 9 mg/kg given with water (group 3; n = 16). Of the 48 children (45 with Plasmodium falciparum malaria, 2 with Plasmodium vivax malaria, and 1 with mixed-species malaria), 2 in group 2 did not attend all follow-up assessments. All regimens were well tolerated, with no serious adverse events. There were no clinically significant changes in pulse, blood pressure, rate-corrected electrocardiographic QT, routine biochemistry/hematology, or hearing after treatment. Fever clearance was prompt. Mean 50% parasite clearance times were 4, 4, and 5 h for groups 1, 2, and 3, respectively. One group 1 patient had PCR-confirmed P. falciparum recrudescence at day 23; four had PCR-confirmed P. falciparum reinfections on day 28 or 42; and three had P. vivax infections detected on day 42. The only recurrent parasitemia in groups 2 and 3 occurred in a group 2 child who developed a P. vivax infection on day 42. Day 14 gametocyte positivity levels were 20%, 27%, and 9% in groups 1, 2, and 3, respectively. The lower single ART-NQ dose was associated with relatively frequent recurrence of parasitemia, but the prolonged gametocytemia in all three groups has implications for the transmission of malaria. Copyright © 2012, American Society for Microbiology. All Rights Reserved.